Open Science Laboratory for Manufacturing: an education tool to contribute to sustainability - Castro, Helio (2021)
This paper presents a Cyber Physical System (CPS) laboratory based on Open Design, called Open Science Laboratory for Manufacturing (OSLab4Man), with educational and research purpose and the potential contribute and (direct and indirect) effects regarding the 17 Sustainable Development Goals (SDGs). A short introduction describing the 17 SDG, the education for sustainability role, and the relevance of the framed CPS. A literature review of CPS laboratories that are addressed to sustainability is presented. The OSLab4Man is describe in the educational purpose lens. Then, the contribute of the OSLab4Man as an education tool for sustainability regarding the 17 SDGs is reflected. Finally, the conclusions of this work and future works are highlighted.